URETERAL STENTING AND URINARY STONE MANAGEMENT : A SYSTEMATIC REVIEW - Ramadhani, Rizkia Amal (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Urolithiasis is a burdensome condition impacting healthcare systems, has seen transformative advancements in ureteroscopy with smaller instruments and laser lithotripsy. While ureteric stenting after ureteroscopy lithotripsy is widely practiced, its necessity in uncomplicated cases remains controversial, with potential complications necessitating further comparative studies for conclusive recommendations. Method: This study followed the 2020 PRISMA guidelines to ensure research alignment with necessary standards for accuracy. Articles were retrieved from databases including PubMed database in November 2023.  Result: The search strategy produced a total of 9 results. Upon reviewing the titles and abstracts, we identified 8 papers that met the criteria for inclusion. Initially, 8 articles were excluded from consideration as they were written in a review format. After a thorough evaluation of the full-text papers, we ultimately included five papers in the final analysis, consisting of prospective observational analysis, retrospective studies, and a randomized control trial. Conclusion: Ureteral stents, crucial in urolithiasis treatment, present challenges due to patient discomfort and limited adoption of symptom-reducing strategies, hindered by knowledge gaps and the absence of well-powered trials. Postoperatively, unstented approaches are favored, and the double pigtail stent with an extraction string outperforms standalone stents, offering prompt relief and avoiding additional procedures. In the context of retrograde intrarenal surgery (RIRS) with a ureteral access sheath (UAS), routine preoperative stenting is unnecessary, with no significant impact on stone-free rates (SFR) or complications. Research into an ideal ureteral stent and the resolution of preoperative hydronephrosis after ureteroscopy continues.